Wokół prawnego pojęcia żywności - Leśkiewicz, Katarzyna (Wydawnictwo Naukowe UAM, 2015)
An attempt has been made in the paper to identify certain common elements, if any, found in the legal concepts of food and an agricultural produce. An analysis of different interpretations of food in judicial decisions of the Polish administrative courts has identified some controversies regarding the notion of food. Of particular practical difficulty seems to be assigning particular types of food to food categories in the meaning provided in Regulation (EC) 172/2002. Administrative bodies applying food law sometimes take a view that the nutrition value of a product is a determining criterion deciding whether a given product is food. Likewise consumers also expect food to provide beneficial effects on the organism, when eaten, while from the legal point of view food need not have a nutritional value to pass as food. In consequence, there are many different preparations may be and are considered food despite the fact that they do not contain any nutritive value.

L’autrice ha provato a individuare eventuali elementi comuni tra i concetti giuridici di alimento e prodotto agricolo. Le interpretazioni del concetto di alimento nelle pronunce dei tribunali amministrativi polacchi rivelano che intorno a questo termine insorgono controversie. Difficoltà particolari appaiono soprattutto nell’ambito dell’assegnazione di alcuni tipi di alimento alla categoria alimenti ai sensi del regolamento n. 178/2002. Gli Enti amministrativi applicando le disposizioni della legislazione alimentare al fine di qualificare un prodotto in termini di alimentare assumono a volte come criterio – il valore nutritivo in esso contenuto, al pari dei consumatori che si aspettano infatti che la nutrizione porti bene-fici all’organismo. Intanto, dal punto di vista giuridico, l’alimento non deve essere dotato di nessun valore nutrizionale, nonché diversi preparati e prodotti, senza valori nutrizionali, possono essere e vengono riconosciuti come alimenti ai sensi del regolamento n. 178/2002.
The legal concept of food
Intorno al concetto giuridico di alimento